Successful pericardiotomy with drainage of the pericardial cavity in case of multimorbid patient - N.M. Seredyuk; A.V. Sudus; I.M. Budzan; S.M. Hrychynyuk; V.В. Tomyn; N.V. Rohiv; M.V. Bielinskyi; A.Ya. Vasylyshyn (Кардіохірургія та інтервенційна кардіологія)
The case of cardiac tamponade late (34 days) after off-pump coronary artery bypass grafting using internal thoracic arteries as bypass grafts is presented. Multimorbidity of the patient included combination of causal diseases (atherosclerosis, coronary artery atherotrombosis), a number of complicated conditions (two myocardial infarctions, left ventricular aneurysm, cardiac tamponade, acute and chronic heart failure), competitive diseases (peptic ulcer, pancreatitis, obesity, umbilical hernia). Pericardiotomy was performed for treatment of the cardiac tamponade and pericardial drainage, since pericardial puncture with aspiration would pose a serious risk to the patient's life. With occurrence of pericardial effusion (pretamponade) and acute decompensated heart failure – cardiac tamponade an emergency care should include pericardiotomy with drainage of the pericardial cavity. This algorithm should be known not only to cardiac surgeons, but also to interventional and therapeutic cardiologists.